2018
DOI: 10.1002/smll.201800691
|View full text |Cite
|
Sign up to set email alerts
|

Competing Mechanisms for Photocurrent Induced at the Monolayer–Multilayer Graphene Junction

Abstract: Graphene is characterized by demonstrated unique properties for potential novel applications in photodetection operated in the frequency range from ultraviolet to terahertz. To date, detailed work on identifying the origin of photoresponse in graphene is still ongoing. Here, scanning photocurrent microscopy to explore the nature of photocurrent generated at the monolayer-multilayer graphene junction is employed. It is found that the contributing photocurrent mechanism relies on the mismatch of the Dirac points… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…To visualize the spatial-resolved photoresponse of the device, SPCM was performed at the zero source–drain voltage ( V ds = 0 V) with low-power 633 nm laser scanning over the device, as illustrated in Figure a,b. SPCM has been previously employed to investigate the photoelectric and electrical properties of many 2D materials, such as graphene and layered TMDCs. , Figure c,d shows the photocurrent images of the pristine WSe 2 FET measured at V g = ±40 V. We observed two photocurrent maxima with opposite polarities appearing at the edges of the contact electrodes, where lateral electric fields were created by Schottky junctions. In contrast, only one localized photocurrent response was observed for the partially p-doped WSe 2 FET at both positive and negative V g (Figure e,f).…”
Section: Resultsmentioning
confidence: 87%
“…To visualize the spatial-resolved photoresponse of the device, SPCM was performed at the zero source–drain voltage ( V ds = 0 V) with low-power 633 nm laser scanning over the device, as illustrated in Figure a,b. SPCM has been previously employed to investigate the photoelectric and electrical properties of many 2D materials, such as graphene and layered TMDCs. , Figure c,d shows the photocurrent images of the pristine WSe 2 FET measured at V g = ±40 V. We observed two photocurrent maxima with opposite polarities appearing at the edges of the contact electrodes, where lateral electric fields were created by Schottky junctions. In contrast, only one localized photocurrent response was observed for the partially p-doped WSe 2 FET at both positive and negative V g (Figure e,f).…”
Section: Resultsmentioning
confidence: 87%
“…Consequently, this limits the energy dissipation for photo-excited carriers, creating a population of electrons with a large effective temperature. Although PTE has been shown to dominate in graphene junctions devices, the presence of photovoltaic (PV) effects cannot be excluded, as it has been recently reported in single/multi-layer graphene junctions [ 56 ].…”
Section: Light Detection In Graphene-based Devicesmentioning
confidence: 99%
“…PVE can also dominate photocurrent in the junction, which is consistent with the built-in electric field all along. Zhang et al found that the dominant mechanism depended on the separation of a Dirac point for both side graphene [180]. They fabricated a monolayer/multilayer graphene junction and acquired its photocurrent mapping, as shown in Fig.…”
Section: Scanning Photocurrent Microscopymentioning
confidence: 99%